Knockdown of IGF-1R Triggers Viral RNA Sensor MDA5- and RIG-I-Mediated Mitochondrial Apoptosis in Colonic Cancer Cells - Shu-Qing Wang; Xiang-Yu Yang; Xin-Feng Yu; Shu-Xiang Cui; Xian-Jun Qu (Elsevier, 2019)
The important role of insulin-like growth factor-1 receptor (IGF-1R) in tumorigenesis has been well established. The classical model involves IGF-1R binding to IGF-1/2, the following activation of PI3K-Akt-signaling cascades, driving cell proliferation and apoptosis inhibition. Here we report a new signal transduction pathway of IGF-1R in the intestinal epithelium. Using heterozygous knockout mice (Igf1r+/−), we analyzed the expressions of viral RNA sensors MDA5 and RIG-I in the intestinal epithelium. Igf1r+/− mice exhibited higher MDA5 and RIG-I than wild-type (WT) mice, indicating that knockdown of IGF-1R could trigger MDA5 and RIG-I. IGF-1R knockdown-triggered MDA5 and RIG-I were further investigated in human colonic cancer cells. Increased MDA5 and RIG-I were clearly seen in the cytoplasm in cancer cells as well as normal human colonic cells with silenced IGF-1R. Notably, the upregulations of MDA5 and RIG-I was not affected by blockage of the PI3K-Akt pathway with LY294002. These results suggested a new signal transduction pathway of IGF-1R. Importantly, IGF-1R knockdown-triggered MDA5 and RIG-I resulted in colorectal cancer apoptosis through activation of the mitochondrial pathway. These in vitro observations were evidenced in the azoxymethane (AOM)-dextran sulfate sodium (DSS) colorectal cancer model of mice. In conclusion, knockdown of IGF-1R triggers viral RNA sensor MDA5- and RIG-I-mediated mitochondrial apoptosis in cancer cells. Keywords: IGF-1R, viral RNA sensors, MDA5, RIG-I, mitochondrial apoptosis